Characterization and modelling of genetic parts - Lee, Michele Shi Min (2015)
The successful engineering of genetic circuits or biological systems relies chiefly on the properties of the bioparts being utilized. In order to create a model that accurately predicts the attributes and behavioral changes of these genetic components under different conditions, the characteristics of different promoters on varying backbone constructs were rigorously studied. The first characterization carried out on 3 P-series promoters: P21, P26 and P51 on moderate copy-number SVC backbone yielded an average GFP/OD value of 5719.807, 4134.648 and 4969.320 RFU respectively during exponential phase, while the second characterization of the same set of promoters on high copy-number PBbE8K backbone resulted in the average exponential GFP/OD values of 9408.075, 4400.231 and 7191.825 RFU in the same order. Comparison between the two results indicate that a higher copy number backbone indeed gave a higher yield of GFP, and for both backbone constructs, P21 is always the strongest promoter, followed by P51 and then P26. At the time when this report was completed, a third set of plasmids containing the target P-series promoters: P26, P51, P53 and P67, and Anderson promoters: J23105 and J23108 on low copy-number PBbS8K backbone were still in the process of being constructed for characterization.